ANALISIS KONSEPTUAL ASAL USUL ANAK: STUDI KOMPARATIF TERHADAP MAZHAB SUNNI DAN SYIAH - Farid, Diana; Abdulah Pakarti, Muhammad Husni; Fathiah, Iffah; Hendriana, Hendriana (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
This study aims to conduct a conceptual analysis of the origins of children in the context of the Sunni and Shiite schools of thought. In the context of Islam, Sunni and Shia schools have different views and practices in several aspects, including the origin of children. Conceptual analysis was carried out by exploring theological understanding and classical literature from both schools to understand the differences and similarities in their views on the origin of children. This study uses a comparative method to compare the perspectives of Sunni and Shia schools regarding the origin of children. First, an analysis of classical Sunni literature, such as hadiths related to conception, fetal development, and child birth is carried out. Then, relevant Shia literature, such as theological and commentary works, is also analyzed to understand their views on the origin of children. After that, the differences and similarities between the two schools of thought were studied and analyzed comprehensively. The results of this study indicate that the Sunni and Shiite schools of thought have different views on the origin of children. Sunnis believe that children come from a physical bond between husband and wife, while Shiites believe that children come from a spiritual bond between husband and wife. In addition, there are differences in views on conception, fetal development, and determining the fate of children between the two schools of thought. This research provides a deeper insight into the differences and similarities between the Sunni and Shia schools of thought in their views on the origin of children. This is important in understanding the diversity of thought within the Islamic religion and can provide a more comprehensive understanding of issues related to family and marriage in Muslim societies.